Strategi Analisis Jabatan pada Perusahaan Penyiaran Media Cyber: Studi Kasus Desa Galis Kabupaten Pamekasan - Syamsul Arifin; Sugianto Sugianto; Nafilatun Khoirun Nisa; Rudy Haryanto (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to examine the application of job analysis strategies in broadcasting companies and how their implementation can improve organizational effectiveness and the quality of information broadcast. Job analysis is important in human resource management because it provides clarity regarding the tasks, responsibilities, and competencies required for each job position. This study employs a qualitative case study method on broadcasting companies using interviews and observations; therefore, the focus of the research is on how job analysis strategies are applied in broadcasting companies. The results indicate that job analysis strategies help establish an efficient organizational structure, clarify the job descriptions of each position, and serve as a foundation for recruitment and training processes. Additionally, job analysis can minimize the spread of fake news by placing human resources in positions that match their competencies. Another important finding is that job analysis directly impacts the professionalism of the editorial team and the quality of information broadcast to the public. Thus, job analysis strategies not only contribute to human resource management but also to the credibility of broadcasting media in the digital information era.